2020
DOI: 10.1051/0004-6361/202038067
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Gravitationally-lensed Objects in HSC Imaging (SuGOHI)

Abstract: Context. Strong lenses are extremely useful probes of the distribution of matter on galaxy and cluster scales at cosmological distances, however, they are rare and difficult to find. The number of currently known lenses is on the order of 1000. Aims. The aim of this study is to use crowdsourcing to carry out a lens search targeting massive galaxies selected from over 442 square degrees of photometric data from the Hyper Suprime-Cam (HSC) survey. Methods. Based on the S16A internal data release of the HSC surve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 66 publications
0
66
0
1
Order By: Relevance
“…The PS1 lens candidates were cross-matched with galaxyscale strong lenses from previous searches with the status of spectroscopally confirmed or candidate systems, by building upon and expanding the current MasterLens database. We compiled grade A and B systems (or equivalent) from a number of recent searches based on optical and near-infrared imaging from DES (Diehl et al 2017;Jacobs et al 2019b,a), CFHTLS (More et al 2016;Jacobs et al 2017), KiDS (Petrillo et al 2017(Petrillo et al , 2019Li et al 2020), DESI (Huang et al 2020a), and HSC (Wong et al 2018;Sonnenfeld et al 2018Sonnenfeld et al , 2020Jaelani et al 2020). Since our network may also be sensitive to lensed quasars with colors and configurations similar to our mock lenses, we also cross-matched with the all-sky database of ∼220 confirmed lensed quasars in the literature (Lemon et al 2019, and references therein) 12 , and with previously identified lensed quasars from HSC (Chan et al 2020) and from PS1 (Rusu et al 2019).…”
Section: Final Candidates From Visual Inspectionmentioning
confidence: 99%
“…The PS1 lens candidates were cross-matched with galaxyscale strong lenses from previous searches with the status of spectroscopally confirmed or candidate systems, by building upon and expanding the current MasterLens database. We compiled grade A and B systems (or equivalent) from a number of recent searches based on optical and near-infrared imaging from DES (Diehl et al 2017;Jacobs et al 2019b,a), CFHTLS (More et al 2016;Jacobs et al 2017), KiDS (Petrillo et al 2017(Petrillo et al , 2019Li et al 2020), DESI (Huang et al 2020a), and HSC (Wong et al 2018;Sonnenfeld et al 2018Sonnenfeld et al , 2020Jaelani et al 2020). Since our network may also be sensitive to lensed quasars with colors and configurations similar to our mock lenses, we also cross-matched with the all-sky database of ∼220 confirmed lensed quasars in the literature (Lemon et al 2019, and references therein) 12 , and with previously identified lensed quasars from HSC (Chan et al 2020) and from PS1 (Rusu et al 2019).…”
Section: Final Candidates From Visual Inspectionmentioning
confidence: 99%
“…On the other hand, Jacobs et al (2019b) simulated 10,000 z > 0.8 elliptical galaxies with lensed features superimposed, and found that 90% of the simulated lenses can be recovered with these two colour-colour cuts. In addition, we examine the colour distributions of strong-lens candidates discovered in the HSC footprint by the Survey of Gravitationally-lensed Objects in HSC Imaging (SuGOHI) project (Sonnenfeld et al 2018;Wong et al 2018;Chan et al 2020;Jaelani et al 2020;Sonnenfeld et al 2020). Every SuGOHI strong-lens candidate is assigned a grade from A (definite), B (probable), or C (possible) and a lens type from GG (galaxy-galaxy), GQ (galaxy-quasar), CG (cluster/group-galaxy), or CQ (cluster/group-quasar).…”
Section: Datamentioning
confidence: 99%
“…They span a wide redshift range from 0.2 to 1.0 2 . We note that candidates from Sonnenfeld et al (2020) are not considered here because some GG strong-lens candidates therein are actually cluster-or group-scale lenses. Among the selected 99 SuGOHI strong-lens candidates, 92 (or ≈ 93%) further pass the colourcolour cuts in criteria 13-14.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We develop here new supervised neural networks for automated selection of galaxy-scale strong lenses in large-scale multiband surveys, using the Hyper-Suprime Cam Subaru Strategic Program (HSC-SSP; Aihara et al 2018) for testing on images approaching the expected depth and quality of the Rubin Observatory Legacy Survey of Space and Time (LSST) final stacks (see Ivezić et al 2019). Previous non-machine learning identification of galaxy-, group-, and cluster-scale lenses from the Survey of Gravitationally lensed Objects in HSC Imaging (SuGOHI; Sonnenfeld et al 2018Sonnenfeld et al , 2019Sonnenfeld et al , 2020Wong et al 2018;Chan et al 2020;Jaelani et al 2020Jaelani et al , 2021, hereafter S18, S20, W18 for SuGOHI-g) offers an independent observational set to test our classification completeness. In this Letter we validate our deep learning pipeline and present new high-confidence galaxy-scale lens candidates with wide image separations from the Wide layer of the HSC survey, which is only 1 mag shallower than LSST ten-year stacks, and has sufficient sky coverage for lens searches.…”
Section: Introductionmentioning
confidence: 99%